Global ocean sediment composition and burial flux in the deep sea - Hayes, Christopher T.; Costa, Kassandra M.; Anderson, Robert F.; Calvo, Eva; Chase, Zanna; Demina, Ludmila L.; Dutay, Jean-Claude; German, Christopher R.; Heimbürger-Boavida, Lars-Eric; Jaccard, Samuel L.; Jacobel, Allison; Kohfeld, Karen E.; et al. (Global biogeochemical cycles, 2021)
Quantitative knowledge about the burial of sedimentary components at the seafloor has wide-ranging implications in ocean science, from global climate to continental weathering. The use of 230Th-normalized fluxes reduces uncertainties that many prior studies faced by accounting for the effects of sediment redistribution by bottom currents and minimizing the impact of age model uncertainty. Here we employ a recently compiled global data set of 230Th-normalized fluxes with an updated database of seafloor surface sediment composition to derive atlases of the deep-sea burial flux of calcium carbonate, biogenic opal, total organic carbon (TOC), nonbiogenic material, iron, mercury, and excess barium (Baxs). The spatial patterns of major component burial are mainly consistent with prior work, but the new quantitative estimates allow evaluations of deep-sea budgets. Our integrated deep-sea burial fluxes are 136 Tg C/yr CaCO3, 153 Tg Si/yr opal, 20Tg C/yr TOC, 220 Mg Hg/yr, and 2.6 Tg Baxs/yr. This opal flux is roughly a factor of 2 increase over previous estimates, with important implications for the global Si cycle. Sedimentary Fe fluxes reflect a mixture of sources including lithogenic material, hydrothermal inputs and authigenic phases. The fluxes of some commonly used paleo-productivity proxies (TOC, biogenic opal, and Baxs) are not well-correlated geographically with satellite-based productivity estimates. Our new compilation of sedimentary fluxes provides detailed regional and global information, which will help refine the understanding of sediment preservation.